Implementation of the seven steps of patient safety in primary healthcare - Syam, Nur Syarianingsih; Maryuni, Linda Tri; Hastututi, Siti Kurnia Widi; Putri, Sely Aprianda Syah (Universitas Ahmad Dahlan, 2025)
Public health efforts and first-level individual health efforts organize primary health. One of the quality management indicators is patient safety, the safety steps are building awareness of the value of patient safety, leading and supporting staff, integrating risk reporting activities, developing reporting systems, involving and communicating with patients, learning and sharing experiences about patient safety, and preventing injuries through the implementation of patient safety systems. The study aimed to determine the implementation of the seven steps of patient safety at one of the primary healthcare facilities in Yogyakarta City. Qualitative research with phenomenological design. Determination of research subjects using a purposive sampling technique. The informants selected were the head of health care, the person in charge of individual health efforts, the patient safety team, the quality team, and the person in charge of pharmacy, laboratory, nurses, doctors, and midwives. Data collection techniques used include field observations, interviews, and document review. The results showed that one of the primary health care facilities in Yogyakarta City has implemented seven patient safety steps. The reporting culture has not been fully implemented, and not as much as expected. The patient safety assessment survey was used for the assessment process in patient safety, and there has never been a patient safety training program for primary health care officers. The seven patient safety steps have been implemented, but the incident reporting culture is still less than optimal.